The Challenges of the Elderly Population with Alzheimer#x2019;s and Dementia in Honduras (Global Journal of Management and Business Research, 2019)
The purpose of this paper is to analyze the number of Alzheimer#x2019;s and Dementia incidences occurring in Honduras and afford recommendations to improve public health policies to assist the elderly. According to The Institute for Health Metrics and Evaluation (2016), there has been an increase in the number of Alzheimer#x2019;s incidences in Honduras. Moreover, the number of Alzheimer#x2019;s cases has increased by 51.4% from 2005-2016. The findings suggested that the country needs to consider a reevaluation of public health policies to tackle the influx of Alzheimer#x2019;s incidences in the upcoming years. Though the elderly population stands at a little less than 6% of Honduras; total population (Berm#xFA;dez-Madriz et al., 2011), it is critical that the elderly community be afforded the best possible healthcare services available. Research suggests that most of the elderly community reside in rural areas where minimal healthcare services are available. In the end, the recommendations will be afforded for the improvement of public health policies to assist the elderly and preparedness for the surge of Alzheimer#x2019;s disease in the country.